Hubungan IMT Terhadap Kadar Gula Darah Pada Pasien Diabetes Mellitus Tipe 2: Tinjauan Pustaka - Ighra Afifah; Intanri Kurniati; Selvi Marcellia; Muhammad Ricky Ramadhian (Medula, 2025)
Type 2 diabetes mellitus is a chronic metabolic disease with a steadily increasing prevalence globally, including in Indonesia. One of the main risk factors contributing to the development and severity of type 2 diabetes is obesity, clinically measured by Body Mass Index (BMI). Increased BMI is closely associated with impaired glucose metabolism and insulin resistance, which play a key role in the pathogenesis of type 2 diabetes. This study used a literature review approach by examining various studies analyzing the relationship between BMI and blood glucose levels. The results showed that increased BMI is positively correlated with fasting blood glucose, random blood glucose, and HbA1c levels. Individuals with a higher BMI tend to experience more severe glycemic control disorders. Pathophysiologically, increased adipose tissue, especially visceral fat, produces various inflammatory mediators such as TNF-α and IL-6, which disrupt the insulin signaling pathway, reduce glucose uptake by muscle tissue, and trigger hyperglycemia. Furthermore, dysfunction of adipokine hormones such as decreased adiponectin and resistance to leptin contribute to worsening insulin sensitivity